Searching for New Physics in an Ultradense Environment: A Review on Dark Matter Admixed Neutron Stars - Francesco Grippa; Gaetano Lambiase; Tanmay Kumar Poddar (Universe)
Neutron stars (NSs), among the densest objects in the universe, are exceptional laboratories for investigating the properties of dark matter (DM). Recent theoretical and observational developments have heightened interest in exploring the impact of DM on NS structure, giving rise to the concept of dark matter admixed neutron stars (DANSs). This review examines how NSs can accumulate DM over time, potentially altering their fundamental properties. We explore the leading models describing DM behavior within NSs, focusing on the effects of both bosonic and fermionic candidates on key features such as mass, radius, and tidal deformability. Additionally, we review how DM can modify the cooling and heating processes, trigger the formation of a black hole, and impact gravitational wave (GW) emissions from binary systems. By synthesizing recent research, this work highlights how DANSs might produce observable signatures, offering new opportunities to probe DM’s properties through astrophysical phenomena.